Thermoplastic Polyurethane/Polylactic Acid Blend Foams Loaded With Curcuma longa L. and Hypericum perforatum Extracts Towards Wound Dressing Applications - Bužarovska, Aleksandra; Stanoeva, Jasmina Petreska; Karamanolevski, Predrag; Popa, Andreea Daniela; Dinescu, Sorina; Avérous, Luc (Wiley, 2025)
ABSTRACTThis study aimed to fabricate and evaluate TPU/polylactic acid foams loaded with natural extracts of Curcuma longa L. (C) and Hypericum perforatum (H) for WD application. In the frame of the structure/properties relationships study, different and complementary analyzes for WD materials, such as water contact angles measurements, water vapor transmission rate, water absorption, and extracts release studies were performed, in connection with the structural and thermal characterizations performed using scanning electron microscopy, differential scanning calorimetry and Fourier transform spectroscopy. The water absorption capacity of the blank blend foam and foams loaded with extracts (C and H) was found to be in the range of 8.31% ± 0.27, 90.7% ± 4.1 and 164% ± 4.0%, respectively. The loaded foams presented cumulative extracts release of 45.5% ± 2% (C) and 100% ± 1.1% (H) within 96 h and acceptable water vapor transmission rate in the range of 2088 ± 66 and 3520 ± 991 g·m−2·24 h−1, respectively. Summary, the investigated foams, enriched with both extracts, showed excellent performances in agreement with WD materials requirements, higher cell viability and proliferation compared to the reference foams, as well as non‐cytotoxic effects on human fibroblasts in experimental conditions.